A Review of Fatty Liver Hemorrhagic Syndrome and Its Pathological Changes in Chickens - Sangary, Mohammad (Journal of Natural Sciences – Kabul University, 2025)
Fatty liver hemorrhagic syndrome (FLHS) is a liver degeneration caused by excessive fat deposition in the liver and leading to sudden death in chickens. The main objective of this study is to describe and explain the etiology, pathogenesis, and macroscopic and microscopic pathological changes of the syndrome in chickens. This study began by collecting research articles published in reputable international journals and related websites, and then articles whose content was from previous years and was not recognized as reliable were excluded. The results of this review highlight that on macroscopic examination, the liver is usually large, pale, and friable. Microscopically, the hepatocytes are dilated, and their cytoplasm contains large amounts of intracellular fat. Therefore, it is concluded that the aforementioned syndrome has no cure, but can be prevented by proper farm management, and the only diagnostic method is to observe postmortem changes.